Implikasi Aturan Bebas BMN Terhadap Penertiban Penatausahaan BMN Mengacu PMK 207/PMK.06/2021 : (studi kasus Kementerian XYZ) - Syaiful Ramadhan (Jurnal Manajemen Kewirausahaan dan Teknologi, 2024)
The management of state property in the current era is no longer just administrative, but more advanced thinking in handling state assets and being able to formulate the needs of state property broadly comprehensive accurately and definitely and think how to increase efficiency, effectiveness and create added value in managing assets in order to create orderly management of BMN administrative, physical orderly and legal order. One of them is by regulating BMN carried out at the XYZ ministry, namely through free BMN. This research aims to reorganize state assets that have not been handled properly so that the administration of state assets becomes better and is able to provide the maximum benefit to the state. Based on the review of the free application of BMN to the BMN Administration Regulation, it has a positive impact, one of which is by increasing the percentage of inventory of goods found by 85.4%.